Antitumor Activity of (2E,5Z)-5-(2-Hydroxybenzylidene)-2-((4-phenoxyphenyl)imino) thiazolidin-4-one, a Novel Microtubule-Depolymerizing Agent, in U87MG Human Glioblastoma Cells and Corresponding Mouse Xenograft Model - Qiu Zhang; Xiaojun Liu; Xiue Li; Changlong Li; Hongyu Zhou; Bing Yan (Elsevier, 2013)
Glioblastoma is the most lethal brain cancer. In spite of intensive therapy, the prognosis of patients with glioblastoma is very poor. To discover novel therapeutic agents, we screened a combinatorial compound library containing 372 thiazolidinone compounds using U87MG human glioblastoma cells. (2E,5Z)-5-(2-hydroxybenzylidene)-2-((4-phenoxyphenyl)imino) thiazolidin-4-one (HBPT) was identified as the most potent anti-glioblastoma compound. HBPT inhibits U87MG human glioblastoma cell proliferation with an IC50 of 20 μM, which is almost 5-fold more potent than temozolomide (a widely used drug for treating malignant glioma in the clinic). Mechanistic investigation demonstrated that HBPT is a novel microtubule-depolymerizing agent, which arrests cancer cells at the G2/M phase of the cell cycle and induces cell apoptosis. In the mouse U87MG xenograft model, HBPT elicits a robust tumor inhibitory effect. More importantly, no obvious toxicity was observed for HBPT therapy in animal experiments. These findings indicate that HBPT has the potential to be developed as a novel agent for the treatment of glioblastoma. [Supplementary Tables: available only at http://dx.doi.org/10.1254/jphs.13064FP] Keywords:: thiazolidinone, glioblastoma, microtubule, microtubule-depolymerizing agent, U87MG human glioblastoma cell